Deciphering the Formulation Secret Underlying Chinese Huo-Clearing Herbal Drink - Wang, Jianan; Zhou, Bo; Hu, Xiangdong; Dong, Shuang; Hong, Ming; Wang, Jun; Chen, Jian; Zhang, Jiuliang; Zhang, Qiyun; Li, Xiaohua; Shikov, Alexander N.; Hu, Sheng; et al. (Frontiers in Pharmacology, 2021)
Herbal tea or herbal drink is a traditional beverage prevalent in many cultures around the world. In Traditional Chinese Medicine, herbal drink infused with different types of medicinal plants is believed to reduce the ‘Shang Huo’, or excessive body heat, a status of sub-health. Although it is widely accepted with a huge market, the underlying science of herbal drinks remains elusive. By studying a group of herbs for the drink, the long-term jargon is connected with inflammation of modern immunology through a few pro-inflammatory markers. Studies in vitro and in vivo quantify each herb’s capability to reduce Shang Huo due to their anti-inflammatory capability. The matching of old oriental mystery with Western science logistics explains the rationality of formulating different herbs into one concoction for detoxification and synergism.